Microeletrodos: I. Construção e caracterização - Fertonani, Fernando Luís [UNESP]; Benedetti, Assis Vicente [UNESP] (Editora Unesp, 1997)
Estudou-se e discutiu-se os diferentes métodos de preparação de microfios de Pt pura, Pt-Ir (20%, m/m) e Pt-Rh (10%, m/m) a serem empregados na construção dos respectivos microeletrodos. Os fios de Pt e suas ligas foram obtidos empregando fieiras com diferentes diâmetros. em seguida foi utilizado o procedimento de desgaste eletroquímico em sal fundido (mistura NaNO3/ NaCl 14: a 320oC) para a Pt e em solução 6 molL-1 NaCN + 2 mol L-1 NaOH para a liga de Pt-Ir. Para a caracterização da interface metal-vidro e determinação dos raios geométrico e efetivo foram empregadas as microscopias óptica e eletrônica de varredura, a voltametria cíclica e a cronoamperometria. A condição de selagem foi verificada através dos gráficos da capacitância aparente Cd, corrigida considerando-se a área dos microeletrodos, e a velocidade de varredura, v.

Platinum, platinum-iridium (20 wt.%) and platinum-rhodium (10 wt.%) alloys were prepared as microwires using different methods. Microwires of Pt and its alloys with several diameters were prepared by passing wires of 1 mm of diameter through a drawplate. Afterwards, the Pt microwire was weared electrochemically in a fused salt mixture (NaNO3/NaCl: 4:1; 320°C) applying a square potential wave (1-50 Hz; 2.5 V). Microwires of Pt-Ir and Pt-Rh alloys were prepared applying a sine-shaped AC potential wave (60 Hz, 3-8 V rms), in 6 M NaCN + 2 M NaOH aqueous solution. The characterization of the interface metal-insulating material and the determination of geometric and effective radii of microelectrodes were carried out by means of optical and scanning electron microscopy, cyclic voltammetry and cronoamperometry. The Cd - v plot, where Cd is the apparent capacitance corrected by the electrode area and v the scan potential sweep was used to verify the interface metal-glass sealing conditions.
Microelectrodes: I. Construction and characterization
Keywords: Preparo e selagem de microeletrodos; platina; ligas de platina; Microelectrodes preparation and sealing; Platinum; platinum alloys